The power of the “weak” and international organizations - Duncan Snidal; Thomas Hale; Emily Jones; Claas Mertens; Karolina Milewicz (The Review of International Organizations, 2024)
Abstract By nearly every measure, power in the international system is concentrated, meaning that most states lack significant power resources. And yet international relations theory tends to focus on the behavior of great powers. This special issue instead explores the strategies that “weak” states use in the context of international organizations both to advance their interests and to resist pressure from stronger states. We define weakness as a relative lack of power across one or more dimensions. While the literature, to the extent it has focused on weak actors, has too often defined weakness solely in material terms, we adopt a broader conception that builds on the influential typology of power by Barnett and Duvall~(Barnett and Duvall,~ 2005a , Barnett and Duvall,~ International Organization 59 , 39–75, 2005b ). A multidimensional conceptualization of power allows analysts to show how actors that are weak in one dimension (often material power) may be stronger on other dimensions, giving them greater capacity for action than is often recognized. From this framework we create a typology of “strategies of the weak” that emphasizes the agency of weaker actors to make the most of their positions. The contributions to the special issue, summarized here, illuminate and substantiate many of these strategies across a diverse range of international organizations, understood as both forums and actors. As the articles show, these alternative theoretical mechanisms help explain how and why seemingly weak states sometimes fare better than a simplistic assessment of their material capabilities might suggest. By deepening our understanding of weakness and how it influences state behavior, the volume advances our theoretical understanding of how power is built, wielded, and resisted in and through international organization.
Keywords: 330; Weak actors; Power; Institutional power; Strategies of the weak; International organizations